SIRT7 Is a Prognostic Biomarker Associated With Immune Infiltration in Luminal Breast Cancer - Huo, Qin; Li, Zhenwei; Cheng, Lixin; Yang, Fan; Xie, Ni (Frontiers in Oncology, 2020)
Background: Sirtuin 7 (SIRT7), a protein-coding gene whose abnormal expression and function are associated with carcinogenesis. However, the prognosis of SIRT7 in different breast cancer subtypes and its correlation with tumor infiltrating lymphocytes remain unclear. Methods: The expression and survival data of SIRT7 in patients with breast cancer were analyzed using Tumor Immune Estimation Resource (TIMER), Gene Expression Profiling Interaction Analysis (GEPIA), The Human Protein Atlas (HPA), UALCAN, Breast Cancer Gene-Expression Miner (BC-GenExMiner), and Kaplan-Meier plotter databases. Also, the expression correlations between SIRT7 and immune infiltration gene markers were analyzed using TIMER, and further verified the results using immunohistochemistry. Results: SIRT7 exhibited higher expression levels in breast cancer tissues than the adjacent normal tissues. SIRT7 expression was significantly correlated with sample type, subclass, cancer stage, menopause status, age, nodal status, estrogen receptor (ER), progesterone receptor (PR), and triple-negative status. High SIRT7 expression was associated with poor prognosis in breast cancer-luminal A (overall survival [OS]: hazard ratio [HR] = 1.54, p = 1.70e-02; distant metastasis-free survival [DMFS]: HR = 1.56, p = 2.60e-03). Moreover, the expression of SIRT7 was positively correlated with the expression of IRF5 (M1 macrophages marker, [r = 0.165, p = 1.13e-04]) and PD1 (T cell exhaustion marker, [r = 0.134, p = 1.74e-03]). These results suggested that the expression of SIRT7 was related to M1 macrophages and T cell exhaustion infiltration in breast cancer-luminal. Conclusions: These findings demonstrate that the high expression of SIRT7 indicates poor prognosis in breast cancer, as well as increased immune infiltration levels of M1 macrophages and T cell exhaustion in breast cancer-luminal. Thus, SIRT7 may serve as a candidate prognostic biomarker for determining prognosis associated with immune infiltration in breast cancer-luminal.